2008
DOI: 10.1159/000156596
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Iodine in 24 h Is Associated with Natriuresis and Is Better Reflected by an Afternoon Sample

Abstract: Aims: We aimed to assess the extent of variability in urinary iodine (UI) within a day, to determine the period of the day when UI was better associated with the UI in 24 h, and to study the relationship between UI and urinary sodium. Methods: This cross-sectional study included 60 volunteers. Four urine samples were collected from each participant (A: from breakfast to lunch; B: from lunch to dinner; C: from dinner to bedtime, and D: from bedtime to breakfast) and were compared with the 24-hour sample (calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…This observation is consistent with the knowledge that ingested iodine appears in the urine after an approximate 4-5 hour delay (56). Another cross-sectional study involving 60 volunteers, concluded that UIC from spot samples collected in the afternoon, between lunch and dinner time, have a stronger correlation to urinary iodine concentrations determined by 24hr collection compared to first morning spot samples (57). A 24 hour sample collection of urinary iodine in Denmark also supported the theory of variable iodine excretion throughout the day (58).…”
Section: Urinary Iodine Concentrationmentioning
confidence: 88%
See 4 more Smart Citations
“…This observation is consistent with the knowledge that ingested iodine appears in the urine after an approximate 4-5 hour delay (56). Another cross-sectional study involving 60 volunteers, concluded that UIC from spot samples collected in the afternoon, between lunch and dinner time, have a stronger correlation to urinary iodine concentrations determined by 24hr collection compared to first morning spot samples (57). A 24 hour sample collection of urinary iodine in Denmark also supported the theory of variable iodine excretion throughout the day (58).…”
Section: Urinary Iodine Concentrationmentioning
confidence: 88%
“…There is strong evidence to suggest that collecting afternoon samples to determine UIC will provide a better representation of iodine status (56,57).…”
Section: Risk Of Thyroid Diseasementioning
confidence: 99%
See 3 more Smart Citations